Submarine Groundwater Discharge From Sediments and Sand Boils Quantified by the Mean Residence Time of a Tracer Injection - Schlüter, Michael; Maier, Philipp (Frontiers in Earth Science, 2021)
To quantify submarine groundwater discharge, we developed an inexpensive automated seepage meter that applies a tracer injection and the computation of the mean residence time. The SGD-MRT is designed to measure a wide range of discharge rates from about 30 to 800 cm³/min and allows minimizing backpressures caused by pipe friction or flow sensors. By modifying the inner volume of the flow-through unit, the range of measurement is adjustable to lower or higher discharge rates. For process control and data acquisition, an Arduino controller board is used. In addition, components like temperature, conductivity, and pressure sensors or pumps extend the scope of the seepage meter. During field tests in the Wadden Sea, covering tidal cycles, discharge rates of more than 700 cm³/min were released from sand boils. Based on the measured discharge rates and numerical integration of the time series data, a water volume of about 400 dm3 with a seawater content of less than 12% was released from the sand boil within 7 h.